Incomplete Antenatal Steroid Therapy Can Enhance Outcomes in Preterm Infants with Emergency Conditions - Sebnem Calkavur; Senem Alkan Ozdemir; Ruya Colak; Ezgi Yangin Ergon; Ferit Kulali; Tulin Gokmen Yildirim (Medical Network, 2020)
OBJECTIVE: We aimed to investigate the role of incomplete of antenatal steroid therapy by comparing with no and complete steroid exposure on mortality and morbidity in preterm infants. STUDY DESIGN: This is a prospective, an observational study which includes preterm infants of 32 weeks of gestation and/or ≤1500 grams who were referred to Izmir Dr. Behcet Uz Children's Hospital NICU during the one year period. Infants were divided into three groups according to the administration of antenatal steroid as those who received incomplete-dose antenatal steroid, complete dose steroid therapy and those with no steroid exposure. Intubation at the delivery room, surfactant requirement, the inotropic requirement in the first 72 hours and morbidities associated with prematurity were determined as the primary results. Mortality and bronchopulmonary dysplasia at discharge and stage ≥2 retinopathy were analyzed as secondary outcomes. RESULTS: We found that 54 infants were born with an incomplete dose, 55 infants with complete dose and 38 infants with no steroid therapy. Surfactant requirement, inotropic requirement, and hemodynamically significant patent ductus arteriosus were lower in the steroid exposure group leading to a statistical difference (p <0.05). Also, it was found that mortality and Bronchopulmonary dysplasia was lower in the incomplete and complete dose steroid groups, leading to a statistical difference (p <0.05). CONCLUSION: We speculate that even incomplete dose steroid may reduce mortality by reducing respiratory distress syndrome.